Translational control : mTOR signalling and the use of next-generation sequencing methods - Jackson, Thomas John (2013)
Translation is a multi-stage process comprising initiation, elongation and termination. It has been suggested that the initiation phase is the rate limiting step of this process. In this thesis the contributions of how changes in initiation and elongation rates lead to overall alterations in gene expression pathways were investigated in a number of different systems. It has been shown previously that increased expression of tRNAiMet is associated with tumourigenesis however the precise role of tRNAiMet in this process was unclear. Data obtained from cells with increased tRNAiMet copy number show that the associated increase in proliferation is transient and unlikely to play a major role in cancer. In collaboration with Dr Owen Samson’s group, it was shown that early dysplastic changes in intestinal tumourigenesis are driven by increased translation elongation via mammalian target of rapamycin 1 (mTORC1). It was found that constitutively active mutant K-Ras confers resistance to mTORC1 inhibition, and combined mTORC1/2 inhibition but that these tumours are acutely sensitivity to loss of the mTORC2 component, Rictor. Interestingly, changes in translation elongation rate were also identified in cells cooled to 32oC and this was associated with the reprogramming of gene expression under these conditions. Finally, the use of the next-generation sequencing technique ribosome profiling illustrated some potential challenges of using this approach to infer biologically relevant conclusions. These include: biases in fragment and library generation, limited read depth and statistical inference from low-count data. An alternate library generation method reduced bias, but reads predicted to be highly structured were still over-represented. The use of a newly developed thermostable ligase did not remedy this problem, but this may be due to additional biases associated with the particular ligase used.